Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Padi Sawah di Desa Pagar Jati - Hendra Herianto Gultom; Syahbudin Hasibuan; Khairul Saleh (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
This study is to determine the factors that influence the income of rice farmers in the Pagar Jati Village of Lubuk Pakam sub-district, Deli Serdang Regency. The sampling method used is the proportionate stratified random sampling method. According to information from the Chairperson of Gapoktan (Farmers Group Association) and the Chair of the farmer group in the pre- research implementation, in Pagar Jati Village, Lubuk Pakam Subdistrict there were 477 farmers working on lowland rice which were joined in 8 farmer groups. Data collected in the form of primary data and secondary data. Data analysis that will be used is descriptive and quantitative methods. Descriptive method aims to describe and interpret data that is pleased with the situation that occurs systematically, factually and accurately about the facts and the relationship between variables to get the truth. To determine the hypothesis, the quantitative method is used technically by using a multiple linear regression econometric model. From the results of the study it can be concluded that based on the Deli Serdang UMK (City Minimum Wage) in 2016, the income of lowland rice farmers in Pagar Jati Village, Lubuk Pakam District, Deli Serdang Regency is relatively high, Rp. 3,071,250, - per month and the factors that influence the income of lowland rice farmers in Pagar Jati Village Lubuk Pakam District Deli Serdang Regency  are  fertilizer  prices  and  farmer  education  levels,  while  the  age  of farmers, the experience of farmers and the number of family dependents do not affect the income of rice farmers rice fields.